Uterine Artery Doppler in Complicated Twin Pregnancies - Dagmara Filipecka-Tyczka; Anna Scholz; Monika Szpotańska-Sikorska; Katarzyna Muzyka-Placzyńska; Artur Pokropek; Michał Rabijewski; Bożena Wroczyńska; Marcin Wieczorek; Małgorzata Zielińska; Magdalena Rudzińska; Krzysztof Berbeka; Paulina Pawłowska; et al. (Diagnostics, 2025)
Background: We assessed the relationship between uterine artery (UtA) indices and the occurrence of obstetrical complications in twin pregnancies. Methods: It was a longitudinal, prospective observation of the UtA indices and obstetric outcomes in twin pregnancies between 11 weeks of gestation and delivery. We used a logistic regression model with reliable estimators of standard errors considering the longitudinal structure. In 150 patients with twin pregnancies, 1086 ultrasound examinations were performed. The analysis incorporated nomograms for singletons and dichorionic (DC) twins. Results: In twin pregnancies, we observed a positive relationship between UtA indices and obstetrical complications (OR = 1.32, p = 0.043 for standardized PI and OR = 1.38, p = 0.018 for standardized RI). The risk increased with increasing UtA indices. There was a significant positive relationship between the UtA indices and analyzed pathologies in DC twins. We observed that both DC twins’ UtA indices below the 5th percentile were associated with favorable outcomes, while those above the 95th percentile were associated with adverse outcomes. According to the singleton nomograms, only the UtA PI above the 95th percentile showed significance. In MC twins, only significantly elevated UtA indices above the upper limit of nomogram were associated with adverse outcomes. Conclusions: The UtA nomogram for singleton and DC twins may be used in the prediction of twin pregnancy outcome, but DC nomograms are more accurate. The mechanism of obstetric complications in MC twins differs, and it requires further research. However, it seems that DC twin nomograms can be used in MC twins, but they will be less effective.